(untitled) (Conferencea, 2024)
Each stage of development is inextricably linked with the political and legal culture of the citizens of that time. In this sense, political and legal culture "is considered a determining factor of the national cultural development of the society"1. In other words, political and legal culture is a criterion that forms a person’s ability to "harmonize and protect the interests of the society, the state, the nation, and one’s own interests"2. Necessity of harmony of political and legal culture 1) determination and implementation of the will of the population related to the political and legal life of the country; 2) mobilizing the public for the development of the country, the prospects of the people, the solution of the priority issues facing the society and the state administration system; 3) it is manifested in the way of bringing the national development to a new stage, organizing the public, compacting, determining the laws of the development of the society.